Pengaruh Celebrity Endorsement dan Brand Image Terhadap Minat Beli Produk Honda Mobil di Jakarta (Survey: Pada Konsumen Honda Mobil di Provinsi DKI Jakarta) - Adrian Brodjonegoro; Rosdiana Sijabat (Universitas Batanghari, 2022)
Promotion is a marketing way to inform, remind, or persuade consumers to influence their opinion or achieve a response. Companies carry out promotional strategies because the company's goals vary so they use several forms of promotion. Currently, there are several types of promotions that can be used, including Celebrity Endorsements and Brand Image. The purpose of this study was to determine the effect of Celebrity Endorsement and Brand Image on consumer buying interest in Honda cars in DKI Jakarta Province. The method in this study uses quantitative research and data analysis using simple linear regression and multiple linear regression analysis. The results obtained are Celebrity Endorsements have a positive effect on Interest in Buying Honda Cars in Jakarta, Brand Image has a positive effect on Interest in Buying Honda Cars in Jakarta and Celebrity Endorsements and Brand Image have a positive effect on Interest in Buying Honda Cars in Jakarta..